Public Resistance to the Limited Face to Face Learning Policy During the COVID-19 Pandemic in Islamic Elementary School - Zuhdiyah Zuhdiyah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2023)
The limited face-to-face learning (PTMT policy implemented by the Indonesian government during the COVID-19 pandemic has received two forms of resistance: closed (practiced by teachers, parents, and students) and open (practiced by teachers). This resistance has made it difficult to resume face-to-face learning. As such, this article seeks to illustrate the public's resistance to the PTMT policy and analyze the implications of this resistance. This article relies on data collected from online media as well as interviews with representatives of diverse elements of society. It shows that resistance has been rooted in several factors: familiarity with online learning, concern that health protocols would not be optimally implemented; and economic concerns. This article recommends conducting further research to obtain a deeper and more comprehensive understanding of the public's resistance to PTMT.